2019
DOI: 10.4274/haseki.galenos.2019.5224
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Pharmacy Workers on Rational Drug Therapy: A Cross Sectional Survey

Abstract: Amaç: Eczane çalışanlarının akılcı ilaç uygulamasında rolünü değerlendirmek ve uygulamada eksik kalan noktalara dikkat çekmek. Yöntemler: Anket formu başlıca Türkiye İlaç ve Tıbbi Cihaz Kurumu Akılcı İlaç Kullanımı Dairesinin ''Hastane Eczacı Anketi'nde'' yer alan sorulara ve önceki çalışmalara dayanmaktadır. Aydın Efeler ilçe merkezinde, 182 gönüllü eczane çalışanı yüz yüze görüşme metoduyla çalışmaya katılmıştır. Bulgular: Eczane çalışanları %51,1 oranında ilkokul, ortaokul ve lise mezunudur, %22,5'i eczacıl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…In a study evaluating the RUM physician parameter on this subject and evaluating Inappropriate Antibiotic use in COPD exacerbations, it was observed that most pulmonologists tend to prescribe antibiotics for COPD exacerbations according to the defined GOLD (Chest Diseases COPD diagnosis and treatment guideline) criteria. However, it has been found that some physicians prefer to prescribe antibiotics on their own regardless of the GOLD criteria (19)(20)(21). In another study in which the physician parameter in the RUM was evaluated, researcher assistant physicians working in the Faculty of Medicine Hospital were evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study evaluating the RUM physician parameter on this subject and evaluating Inappropriate Antibiotic use in COPD exacerbations, it was observed that most pulmonologists tend to prescribe antibiotics for COPD exacerbations according to the defined GOLD (Chest Diseases COPD diagnosis and treatment guideline) criteria. However, it has been found that some physicians prefer to prescribe antibiotics on their own regardless of the GOLD criteria (19)(20)(21). In another study in which the physician parameter in the RUM was evaluated, researcher assistant physicians working in the Faculty of Medicine Hospital were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, individuals, patients, physicians, health policies, pharmacists and pharmaceutical companies approach and practices are effective in the society. Limiting the use of non-prescription antibiotics, restricting the use of some medicines without a related branch report, and limiting the medicines intake by calculating the usage dose according to the duration were useful practices (21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%